Harnessing the awe of eclipses to enhance science engagement - Fischer, Heather A.; Sellers, Victoria; Storksdieck, Martin (Frontiers in Astronomy and Space Sciences, 2025)
This study examines the impact of the 2024 Total Solar Eclipse on participants’ feelings of awe, science identity, and interest in science-related activities through structured science engagement events. Drawing on a mixed-methods approach, the research collected data from over 1,300 attendees at NASA-hosted eclipse events across the United States, with follow-up surveys conducted 6 months later. Findings reveal that the eclipse evoked high levels of awe, which remained relatively stable over time. Participants also reported elevated science identity and intentions to engage in future science activities; however, a gap was observed between intention and action. Correlational analyses suggest that awe, science identity, and science engagement are interrelated and mutually reinforcing. These results underscore the potential of awe-inspiring natural phenomena to serve as powerful catalysts for informal science learning and long-term public engagement with science.